2009
DOI: 10.1371/journal.pone.0007774
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation and Biological Functions of Selenium-Binding Protein 1 in Colorectal Cancer In Vitro and in Nude Mouse Xenografts

Abstract: BackgroundIt has been shown that selenium-binding protein 1 (SBP1) is significantly downregulated in different human cancers. Its regulation and function have not yet been established.Methodology and Principal FindingsWe show that the SBP1 promoter is hypermethylated in colon cancer tissues and human colon cancer cells. Treatment with 5′-Aza-2′-deoxycytidine leads to demethylation of the SBP1 promoter and to an increase of SBP1 promoter activity, rescues SBP1 mRNA and protein expression in human colon cancer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
67
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 15 publications
3
67
0
1
Order By: Relevance
“…Although we have not demonstrated clearly the mechanisms underlined the tumor suppressor functions of SBP1, it has been evidenced that SBP1 promoter was hypermethylated in human colon cancer cells and indicated that SBP1 expression in colon cancer was in part controlled through gene silencing [23]. Although decreased expression of SBP1 was demonstrated in GC, more evidence should be provided to identify the tumor suppressive activities of SBP1.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Although we have not demonstrated clearly the mechanisms underlined the tumor suppressor functions of SBP1, it has been evidenced that SBP1 promoter was hypermethylated in human colon cancer cells and indicated that SBP1 expression in colon cancer was in part controlled through gene silencing [23]. Although decreased expression of SBP1 was demonstrated in GC, more evidence should be provided to identify the tumor suppressive activities of SBP1.…”
Section: Discussionmentioning
confidence: 59%
“…SBP1 expression was also closely correlated to the prognosis of many malignant tumors. And recently, overexpression of SBP1 in human colon cancer cell line HCT116 was identified to induce H2O2-mediated apoptosis, inhibit cell migration in vitro and inhibit tumor growth in nude mice, which provide the evidence to show that SBP1 has anti-cancer functions [23]. Furthermore, SBP1 was characterized as a biomarker for schizophrenia [24].…”
Section: Discussionmentioning
confidence: 97%
“…Reduced expression of SBP1 is also associated with poor clinical prognosis among patients with lung adenocarcinoma [30], gastric cancer [36], hepatocellular carcinoma [27], colon cancer [37,38], and breast cancer [41]. Furthermore, our in vitro and in vivo studies have also shown that increasing SBP1 expression in colorectal cancer cells attenuates cancer cell migration and tumor growth in nude mice [42]. Consistent with these findings, knockdown of SBP1 by small interfering RNA (siRNA) in the nontransformed human liver cells results in a substantial increase in cell proliferation index and migration capacity [27], suggesting that SBP1 acts as a tumor suppressor [43], which is further supported by the recent study that SBP1 negatively regulates HIF-1α expression and suppresses the malignant phenotype of prostate cancer cells [44].…”
Section: Introductionmentioning
confidence: 62%
“…It is therefore not clear why this protein appeared downregulated after exposure to sediment C 1 , in the laboratory, comparatively to reference (R-tested) animals. Interestingly, downregulation of SBP1 has been found linked to carcinogenesis in mammal models and it is suspected that this protein mediated ROS (reactive oxygen species) -induced apoptosis of neoplasic or preneoplasic cells (for instance Pohl et al 2009). In accordance, some evidence exists on SBP1 downregulation by oxidative stress (Giometti et al 2000).…”
Section: Discussionmentioning
confidence: 99%